Effects of flapping wing micro air vehicle's pitching angle on stability at low reynolds number - Mowhoub, Mohamed; Abdullah, Ermira Junita (Aerospace Society Malaysia, 2023)
The instability of flapping wing aircrafts makes them difficult to control. As it is challenging to control and puts passengers at risk, it is not currently employed in modern aircraft technology. This study aims to analyze the aerodynamic coefficients of flapping wing aircraft at different flapping angles in order to understand their effects on the aircrafts stability. XFLR5 software was used to calculate the aerodynamics coefficients and longitudinal derivatives in different range of flapping angles from 40° to -40°. This range of flapping angles has been selected for the purpose of this study based on the physical limitations of a mechanical vehicle. Theoretically, an aircraft without a tail is unstable because the main function of a tail is to produce a moment that counters the moment produced by the wings to balance the aircraft. In the presented research, a model has been designed with and without tail, and modeled using XFLR5 to produce the aerodynamics coefficients. Then, MATLAB software was used to develop the longitudinal flight dynamics for the model. The results show that the longitudinal motion is stable for the range of flapping angle between 40° to -40°. The natural frequency increases as flapping angle changes from 0° to 40° and from 0° to -40°. In the meantime, for the short period modes eigenvalue, the real part moves toward the origin as the flapping angle changes from 0° to 40° and from 0° to -40°. On the other hand, for the phugoid modes eigenvalue, the real part moves away from the origin to the left half plane as the flapping angle changes from 0° to 40° and from 0° to -40°.